2013
DOI: 10.1017/s1041610213001166
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of thoughts of death or suicide in depressed older persons

Abstract: In depressed older persons thoughts of death and suicide differ in relevant demographic, social, and clinical characteristics, suggesting that the risks and consequences of the two conditions differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
(72 reference statements)
1
13
1
2
Order By: Relevance
“…Between 11% and 19% of community dwelling older persons reports thoughts of death or death wishes (Rurup et al, 2011a(Rurup et al, , 2011bFässberg et al, 2013), which is only slightly lower compared with prevalence rates among depressed older persons (Szanto et al, 2003;Bogers et al, 2013). Thoughts of death are less closely associated with severity of psychopathology and feelings of self-hatred (Szanto et al, 1996;Bogers et al, 2013). Thoughts of death and thoughts of suicide may thus differentially impact on the course of depressive disorders in older persons.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Between 11% and 19% of community dwelling older persons reports thoughts of death or death wishes (Rurup et al, 2011a(Rurup et al, , 2011bFässberg et al, 2013), which is only slightly lower compared with prevalence rates among depressed older persons (Szanto et al, 2003;Bogers et al, 2013). Thoughts of death are less closely associated with severity of psychopathology and feelings of self-hatred (Szanto et al, 1996;Bogers et al, 2013). Thoughts of death and thoughts of suicide may thus differentially impact on the course of depressive disorders in older persons.…”
Section: Introductionmentioning
confidence: 85%
“…Depressed older patients with suicidal ideation suffer from more severe depressive symptoms compared with depressed patients without suicidal ideation (Bogers et al, 2013). Whether suicidal ideation affects the course of late-life depression remains a matter of debate (Szanto et al, 2001(Szanto et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings agree with Zisook et al (2009) who found that depression severity, concurrent substance abuse and melancholia were associated with TESI in a report from the STAR*D trial. Likewise, other studies have pointed at depression severity, medical, and psychiatric comorbidity (including anxiety) as predictors of suicidal ideation independent of treatment (Alexopoulos et al ., 2009; Bogers et al ., 2013; Shah et al ., 2000; Lenze et al ., 2000; Seo et al ., 2011)…”
Section: Discussionmentioning
confidence: 99%
“…In depressed older adults, suicidal ideation is associated with higher severity of depression, previous suicide attempts, greater medical and psychiatric comorbidity (i.e. panic disorder and alcohol abuse), loneliness, and lower subjective social support [1921]. In a study of Korean elders, depression mediated the relationship of social support and low income with suicidal ideation [22].…”
Section: Recent Findings On Major Depression Schizophrenia and Suicmentioning
confidence: 99%